Agricultural research: a growing global divide? - Pardey, Philip G.; Beintema, Nienke M.; Dehmer, Steven; Wood, Stanley (International Food Policy Research Institute, 2006)
Sustained, well-targeted, and effectively used investments in R&D have reaped handsome rewards from improved agricultural productivity and cheaper, higher quality foods and fibers. As we begin a new millennium, the global patterns of investments in agricultural R&D are changing in ways that may have profound consequences for the structure of agriculture worldwide and the ability of poor people in poor counties to feed themselves. This report documents and discusses these changing investment patterns, highlighting developments in the public and private sectors. It revises and carries forward to 2000 data that were previously reported in the 2001 IFPRI Food Policy Report Slow Magic: Agricultural R&D a Century After Mendel. Some past trends are continuing or have come into sharper focus, while others are moving in new directions not apparent in the previous series. In addition, this report illustrates the use of spatial data to analyze spillover prospects among countries or agroecologies and the targeting of R&D to address specific production problems like drought-induced production risks." Authors' Preface